Design and application of photo-reversible elastomer networks by using the [4πs+4πs] cycloaddition reaction of pendant anthracene groups. (12th October 2016) - Manhart, Jakob; Ayalur-Karunakaran, Santhosh; Radl, Simone; Oesterreicher, Andreas; Moser, Andreas; Ganser, Christian; Teichert, Christian; Pinter, Gerald; Kern, Wolfgang; Griesser, Thomas; Schlögl, Sandra
Abstract: In this work, the photo-reversible [4πs+4πs] cycloaddition reaction of anthracene moieties is employed to impart wavelength dependent properties into carboxylated nitrile butadiene rubber networks. Crosslinking of the side chain functionalized rubber is achieved by UV induced dimerization of pendant anthracene groups at wavelengths above 300 nm whilst a subsequent deep UV exposure (λ = 254 nm) results in a well-defined cleavage of the crosslinks. Crosslink kinetics and photo-reversibility of the dimerization reaction are determined by spectroscopic measurements. The changes in network structure and chain dynamics over multiple crosslinking and cleavage cycles are studied in detail by low field NMR. In thin films, the wavelength dependent changes in solubility are employed for the preparation of reversible photoresists enabling the preparation of 2D microstructures and a switching between negative- and positive-type patterns. Along with thin films, the wavelength dependent modulation of thermo-mechanical properties is also demonstrated for macroscopic samples, which shows the versatility of these optically stimuli-responsive networks. Graphical abstract: Highlights: Synthesis of reversible elastomer networks by exploiting pendant anthracene groups. Photocleavage yield (λ < 300 nm) increases with rising crosslink density. Reversible changes in solubility enable the preparation of switchable photoresists. Fabrication of flexible 2D patterns with good resolution and contrast behavior. Wavelength dependent modulation of thermo-mechanical properties is demonstrated.